CONSTRUCTION AND VALIDATION OF EDUCATIONAL TECHNOLOGY ON INSULIN THERAPY: METHODOLOGICAL STUDY - Adriane Stefanny Rocha Ribeiro; Jéssica Gomes da Silva; Cecília Rafaela Salles Ferreira; José Luis da Cunha Pena; Kaila Correa Santos; Laidiane Dantas Soares Pena; Francineide Pereira da Silva Pena (Universidade Federal do Paraná, 2023)
Objective: to build and validate educational technology on insulin therapy for educational practices of health professionals. Method: methodological study conducted in three stages: construction, between May and September 2019; and content validation and appearance validation, August 2020 to August 2021, in a Public University of Amapá, Brazil. Content validation and appearance validation were performed in single steps with 16 health professionals and with five professionals from other areas respectively. Results: The educational technology was named Serial Album on Insulin Therapy and was available in printed format. It presented a Content Validity Index of 0.91 and an Appearance Validity Index of 1.00. Conclusion: the technology was validated and can be used by primary care health professionals in health educational practices, with a view to promoting teaching-learning about the use of insulin, benefiting the process of care and communication in health care.